Effect of alcohol on health and academic performance of a selected secondary students in Ibadan (2001)
"This paper examined the effect of alcohol use on general health and academic performance of secondary school students in Ibadan. Data were collected through questionnaire from 300 senior secondary school students made up of, 160 males and 140 females. The mean (X) age is 15.9 with age range of 13 to 21 years old and standard deviation (SD) of 2.20. Three hypotheses were tested at 0.05 level of significance with the following test analysis: descriptive statistics, chi-square, ANOV A and t-test. The results showed firstly that, students who abstained from alcohol have a better academic performance, Abstainers X = 202.79; monthly drinking X = 187.93, weekly drinkers (X) = 181.33. Secondly, there was significant different in emotional distress between students who abstained from alcohol and students who used alcohol daily, weekly and monthly drinkers {X2 = 12.96, df = 3, P<0.05), and thirdly male students were found to be more involved in alcohol use that female students (males X = 1.17, females X = 0.86) t = 22.64 df = 298 P<0.05).• Finally, it was concluded that alcohol is a problem among Nigerian youths, which required attention from the government and relevant authorities. Recommendation and implication of the study were highlighted for prevention and control of alcohol use/abuse. "